Practices of Mathematization by Basic Level Mathematics Teachers of Nepal - Acharya, Nara Hari; Pokhrel, Tika Ram; Kunwar, Rajendra (Education and Development, 2025)
The study on the process of mathematization practices applied to teaching mathematics by basic level teachers aimed to explore how the basic level mathematics teachers have been using and practicing mathematization in problem-solving. Twenty-five mathematics teachers of the basic level who had taken teachers' professional development training were the participants of the study. The story-based problems at the basic level were distributed, and their solutions were collected after half an hour. The data were sorted and different solutions to the same problem were considered. It was observed that most of the teachers have been using mathematization in solving problems though they were unknown about it. Some of them were not aware of the visualization of the problems and solving the problem by using the formula directly. The study shows that while teachers are using both vertical and horizontal mathematization, many teachers lack a clear understanding of when and how to apply these methods appropriately. Providing professional development opportunities to mathematics teachers and incorporating mathematization concepts and skills into the curriculum can enhance mathematical thinking skills.